The Corelation of Laboratory Practicum Achievements and Achievements Of The Competence Target Of The Department Of KDPK Clinical Private Vocational School Students - Ika Agustina (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2019)
Abstract: Practice at transcendent laboratory to be required deep prop laboratory practice achievement. Mark sense decrease among laboratories practicing achievement with interest target attainment KDPK so causes its low practicing interest target attainment reverential KDPK clinic its low college student ability because training reducing college student upon at laboratory at the time laboratory skill.Analytic observational korelasional with population is college student as much 40 college students by use of tech total samplings. For independent variable is laboratory practicing achievement, dependen's variable which is practicing interest target attainment KDPK'S clinic. Data measurement utilize check list's sheet and rekapan is target then result acquisition it is analysed by use of Mann Whitney . Result that is gotten from this research laboratories practicing achievement a large part be appreciative AB (42,5% meanwhile practicing interest target attainments KDPK'S clinics a considerable part accomplished targets asP big as 90%. Known by point Mann Whitney p = 0,731 therefore this point more than α  = 0,05. analisis's result points out no relationship among laboratories practicing achievement with interest target attainment KDPK zoom college student midwifery D3 STIKes Patria Husada Blitar year 2012. With marks sense this research is expected college student coaches its skill to get things square succeeding clinic practice.                                                                                                                                                                                                                 Keywords: practice, laboratory, interest